2023
DOI: 10.1111/1440-1681.13754
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH5 inhibits the SIRT3/ACC1 axis to regulate fatty acid metabolism via an m6A‐IGF2BP1‐dependent manner in cervical squamous cell carcinoma

Abstract: Cervical cancer (CC) is the most common malignancy of the female reproductive system, among which cervical squamous cell carcinoma (CESC) is the most common type. The demethylase ALKBH5 has been previously revealed to be downregulated in CC tissue. N6 methyladenine (m6A) is the most common modification in eukaryotic RNAs and is involved in modulating tumour progression. Therefore, we attempted to clarify the ALKBH5 role and mechanism underlying CESC progression.In CESC, patient tissue and control tissue m6A le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In AML, IGF2BP2 stabilizes protein arginine methyltransferase 6 (PRMT6) and subsequently downregulates the expression of the lipid transporter major facilitator superfamily domain containing 2A (MFSD2A), thereby maintaining the function of leukemia stem cells 414 . In CC, depleted levels of the demethylase ALKBH5 indicate an unfavorable prognosis, and ALKBH5 functionally suppresses the expression of silent mating type information regulation 2 homologue 3 and ACC1 in an IGF2BP1‐dependent manner, ultimately inhibiting FA synthesis 415 . In bladder cancer, METTL14 induces lncDBET overexpression, and along with FA binding protein 5 (FABP5), it promotes lipid metabolism and the malignant progression of bladder cancer 416 .…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In AML, IGF2BP2 stabilizes protein arginine methyltransferase 6 (PRMT6) and subsequently downregulates the expression of the lipid transporter major facilitator superfamily domain containing 2A (MFSD2A), thereby maintaining the function of leukemia stem cells 414 . In CC, depleted levels of the demethylase ALKBH5 indicate an unfavorable prognosis, and ALKBH5 functionally suppresses the expression of silent mating type information regulation 2 homologue 3 and ACC1 in an IGF2BP1‐dependent manner, ultimately inhibiting FA synthesis 415 . In bladder cancer, METTL14 induces lncDBET overexpression, and along with FA binding protein 5 (FABP5), it promotes lipid metabolism and the malignant progression of bladder cancer 416 .…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%
“… 414 In CC, depleted levels of the demethylase ALKBH5 indicate an unfavorable prognosis, and ALKBH5 functionally suppresses the expression of silent mating type information regulation 2 homologue 3 and ACC1 in an IGF2BP1‐dependent manner, ultimately inhibiting FA synthesis. 415 In bladder cancer, METTL14 induces lncDBET overexpression, and along with FA binding protein 5 (FABP5), it promotes lipid metabolism and the malignant progression of bladder cancer. 416 In GBM, constitutively activated EGFR/SRC/ERK pathway results in YTHDF2 overexpression and subsequently downregulate LXRA and HIVEP2 expression, thereby disrupting cholesterol homeostasis and sustaining GBM tumorigenesis.…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%
“…ALKBH5 attenuated stability of SIRT3 mRNA in an IGF2BP1-dependent manner, further reduced ACC1 level repress its deacetylation, thus suppresses fatty acid synthesis to modulate CESC lipid metabolism. 327 …”
Section: Rna Modifications and Cellular Metabolismmentioning
confidence: 99%
“…Liu et al [40] showed that ACC depletion suppresses de novo fatty acid synthesis and mitochondrial beta-oxidation in the synthesis of acetyl-Coa carboxylase castration-resistant prostate cancer cells. Moreover, many studies have found that regulating fatty acid levels by interfering with ACC expression can help inhibit tumor growth [41][42][43]. Therefore, ACC1 inhibition has become an appealing choice for antitumor therapy [43,44].…”
Section: Fatty Acid Metabolismmentioning
confidence: 99%